Variation of Faba Beans (Vicia faba L.) Traits Induced By Heat, Electric Shock and Mutagen Nitrous Acid (Baghdad Science Journal, 2015)
This research was carried out to determine the impact of heat shock, electric shock and seeds in soaking nitrous acid mutagen solution on three cultivars of faba beans plant (Zaina, Aguadulce and Local) at the year 2012-2013. Factorial experiment was arranged in randomized complete block design (RCBD) with three replicates were used. The results showed that heat shock lead to early plants of 50% in flowering and an increase in the number of branches/plant and the number of seeds/pod compared to other treatments, whereas the seeds soaked in nitrous acid mutagen solution gave the highest plant height, leaf area index, number of pods/plant, seed weight, seed yield kg/ha, and did not differ significantly with treatment of electric shock in the protein yield(kg/ha). Zaina cultivar was superior over other cultivars in early to 50% flowering, number of branches/plant, number of pods/plant and seed weight, while gave the lowest value in plant height. Significant differences also observed for the interaction between cultivars and treatments. Zaina cultivar with heat shock treatment gave less number of days to 50% flowering, highest number of branches/plant and the number of seeds/pod, either when seeds soaked in nitrous acid mutagen solution given the highest plant height of plant, highest mean of seed weight, seed yield kg/ha and did not differ significantly with local variety in the number of pods/plant trait .